2022
DOI: 10.1186/s12936-022-04086-w
|View full text |Cite
|
Sign up to set email alerts
|

Permethrin-treated baby wraps for the prevention of malaria: results of a randomized controlled pilot study in rural Uganda

Abstract: Background Progress against malaria has stalled and may even be slipping backwards in high-burden countries. This is due to a range of factors including insecticide resistance and mosquito feeding behaviours that limit contact with widely-employed interventions including long-lasting insecticidal nets and indoor-residual spraying. Thus, further innovations in malaria control are urgently needed. Methods The pilot was a randomized, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Previous studies suggest that mechanisms by which malnutrition could protect against malaria infection include improved ability of malnourished children to produce certain cytokines in response to stimulation by specific malarial antigens 29 and potential confounding resulting from improved malaria preventive measures for ill children, 15 as malnutrition can be accompanied by other illnesses. In particular, because newborns and infants are usually wrapped with clothing and carried on the back of the mother or caregiver in most African countries, 30 they may have had additional protection from exposure to mosquitoes. One study explored how to use this practice by treating clothing for added protection from malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that mechanisms by which malnutrition could protect against malaria infection include improved ability of malnourished children to produce certain cytokines in response to stimulation by specific malarial antigens 29 and potential confounding resulting from improved malaria preventive measures for ill children, 15 as malnutrition can be accompanied by other illnesses. In particular, because newborns and infants are usually wrapped with clothing and carried on the back of the mother or caregiver in most African countries, 30 they may have had additional protection from exposure to mosquitoes. One study explored how to use this practice by treating clothing for added protection from malaria.…”
Section: Discussionmentioning
confidence: 99%
“…One study explored how to use this practice by treating clothing for added protection from malaria. 30 Therefore, infants in general and those with illnesses and weaker immunity, in particular, may be kept closer physically and cared for differently.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high level of subject participation and retention in the pilot study [ 34 ], we expect most mother-infant pairs to complete all study activities. Missing data due to dropout or missed clinic visits are anticipated to be uncommon (≤5% missing), so a complete case analysis is planned.…”
Section: Methodsmentioning
confidence: 99%
“…falciparum malaria in children 6–24 months of age in western Uganda. This trial builds on the work of a pilot feasibility study conducted in 2019, the results of which indicated that permethrin-treated baby wraps were well-tolerated and broadly acceptable, while adverse events were infrequent and mild [ 34 ]. These findings support the need for larger trials to evaluate the efficacy of the permethrin-treated lesus .…”
Section: Introductionmentioning
confidence: 99%
“…Como exemplos destes trabalhos se pode citar (ALSERKAL et al, 2020), (LINNAN et al, 2020), (SHIMA et al, 2021) e (BOYCE et al, 2022.…”
Section: Trabalhos Correlatosunclassified